Refined endoscopic technique combined with cold forceps polypectomy for diminutive colorectal polyps - Xue-Man Wang; Qin-Wei Xu; Yu-Zhen Bi; Quan Luo; Bo Lian; Jian Dong; Xin-Tong Jiang; Jun Zhang (World Journal of Gastrointestinal Surgery, 2026)
BACKGROUND The most appropriate endoscopic management for small (≤ 5 mm) colorectal adenomas has not yet been well established. Although cold snare polypectomy (CSP) is recommended by the guidelines, cold forceps polypectomy (CFP) remains a popular technique because it is easy to perform. However, previous data have suggested that a modified CFP technique using jumbo biopsy forceps, post-resection narrow-band imaging (NBI), and submucosal injection can yield high en bloc resection rates. AIM To assess the performance and safety of the modified CFP-NBI-flush method vs CSP for the management of diminutive colorectal adenomas. METHODS This retrospective study included 124 patients harboring 170 eligible diminutive adenomas (≤ 5 mm) who underwent colonoscopy at the Shaoxing People’s Hospital (Shaoxing, China) between November 2023 and December 2024. Polyps were categorized into CFP-NBI-flush (n = 86) and CSP (n = 84) groups according to the technique documented in the endoscopy report. Polyps were used as the unit of analysis for polyp-level outcomes, including recurrence. The primary endpoint was 6-month local recurrence rate, and the secondary endpoints were en bloc resection rate, procedure duration, cost(s), and complications. RESULTS Local recurrence rates were 2.6% (2/78) in the CFP-NBI-flush group and 7.5% (6/80) in the CSP group, with no statistical differences (P = 0.277). Despite a higher en bloc resection rate with CSP (92.9% vs 81.4%, P = 0.038), CFP-NBI-flush resulted in shorter procedural duration (median, 32.0 seconds vs 50.5 seconds; P < 0.001), was less expensive (349.7 ± 30.6 CNY vs 398.3 ± 55.1 CNY; P < 0.001), and yielded 100% specimen retrieval (92.9% for CSP; P = 0.013). Immediate bleeding rates (5.8% vs 8.3%, P = 0.563) and other complications (delayed bleeding, perforation) did not differ significantly between the two groups (both 0%). The use of metal clips between the two groups was also similar (5.8% vs 8.3%; P = 0.563). CONCLUSION The CFP-NBI-flush technique showed a 6-month local recurrence rate comparable to that of CSP, and offered advantages in terms of procedural efficiency, specimen retrieval, and cost.